Pneumocystis carinii Pneumonia in HIV — Investigate or Just Treat? - Steven Kesten (Canadian Respiratory Journal, 1994)
Pneumocystis carinii pneumonia (PCP) is an extremely common manifistation of the acquired immunodeficiency syndrome (AIDS) resulting from infection with the human immunodeficiency virus (HIV). Most episodes present in a fairly typical manner with increased dyspnea and/or a nonproductive cough, a diffuse interstitial pattern on chest readiograph and an elevated alveolar-arterial oxygen gradient. The pattern has been so typical of the disorder that empirical therapy without microbiological proof of disease is often imitated by primary care physicians. This strategy has not been tested in controlled clinical trials although decision analysis models have attempted to evaluated it, it's liekly reasonable to choose empirical antimicrobial therapy in specific clinical settings such as: (a) typical radiographic picture in a person with dyspnea and/or nonproductive cough. presence of HIV and a CD4 count of less than 200 cells/mm3:(b) previous PCP, typical appearance and the patient is known to tolerate standard anti-PCP medications: and (c) high clinical suspicion in a patient who refuses bronchoscopy yet desires treatment or where bronchoscopy cannot he performed. However, early bronchoscopy should strongly he considered when the chest radiograph is not typical of P carinii infection or if there is failure to respond after a predefined period.